ANALYSIS INFORMATION SYSTEM FOR GOODS INVENTORIES - Teguh Prasetio; Drs. Sunarto Usna, MMSI Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2008)
Information systems currently used by many people as information that helps in terms ofdata acquisition. So also with the management of the stocks in the computer dataprocessing is still a lot of difference constraints with the number of physical goods thatare in the field. For it needs to make a management information system in order tofacilitate the sale of goods is based on the available inventory in a timely, precise, andaccurate. By using a management information system, work will become easier andtimely. For that the theory of the strong foundation necessary to support the information.